Literature Review of Traditional Siddha Diagnostic Method of Manikkadai Nool - Rakulini, R.; Rajarajeshwari, A.; Victoria, S. (Journal of Complementary and Alternative Medical Research, 2019)
Introduction: Siddha Medicine is a system of traditional medicine originating in ancient Tamil Nadu in South India and Sri Lanka. Traditionally, it is taught that the siddhars laid the foundation for this system of medicine. Siddha system has a unique diagnostic method to identify the diseases and their causes. Manikkadai nool is one of the diagnostic tool. It is explained in the Agasthiyar Soodamani Kajiru Soothiram by Saint Veadammamuni in Pathinen Siddhar Naadi Nool. Aim: The primary aim of this study was to do a literature review and documentation of traditional siddha diagnostic method of Manikkadai Nool. Study Setting: Government Siddha Medical College, Palayamkottai from March to August 2019. Methodology: It is a review of relevant literatures on traditional siddha diagnostic method of manikkadai nool. Data for the literature review were collected from related literatures and websites. Collected data were processed and statistically analyzed by a simple statistical method using Microsoft Excel. Results and Discussion: Manikkadai Nool is a parameter to diagnose the state of disease by measuring the circumference of the wrist by means of a thread and then dividing the measured circumference with the patient’s finger. By this measurement the disease can be diagnosed. When the Manikkadai nool is 11 finger breadth (fbs), the person will be stout and he/she will live a healthy life for many years. When the Manikkadai nool measures from 4 to 6, it indicates bad prognosis of disease and the severity of the illness will be high and it leads to death. One of the research articles said that the cardiac diseases and uterine fibroids had a more predilection than other diseases of Manikkadai Nool measure falling in the fringe range of 10-10.75 finger breadths. Conclusion: This literature review provides useful documented evidence on the siddha diagnostic methods of Manikkadai Nool. However, there is need to more clinical studies to validate the measurements.
Keywords: Manikkadai nool; Siddha; Diagnostic methods; Traditional; Medicine